Uterine Tumor Resembling Ovarian Sex-Cord Tumors Initially Diagnosed as a Prolapsed Fibroid - Fernando Augusto Rozário Garcia; Vanessa Pereira Gaigher; Rodrigo Neves Ferreira; Antônio Chambô Filho (Case Reports in Obstetrics and Gynecology)
Background. First described in 1945 by Morehead and Bowman, uterine tumors resembling ovarian sex-cord tumors (UTROSCT) are rare tumors of the uterine body that tend to occur in menopausal women presenting with abnormal vaginal bleeding, abdominal pain, and increased uterine volume. UTROSCT are usually diagnosed from incidental histological findings following hysterectomy performed due to a suspected endometrial polyp or uterine fibroids. Objective. To report on a 46-year-old patient with abnormal vaginal bleeding. At physical examination, a pediculated nodular lesion was found protruding from the external cervical os. Histopathology of the resected lesion led to a diagnosis of UTROSCT. Total abdominal hysterectomy with bilateral adnexectomy was then performed. The patient is currently undergoing regular outpatient follow-up, with no evidence of disease after one year. Methods. Data were retrieved from the patient’s records, and macroscopic and microscopic images of the tumor were obtained. Discussion. Reports of metastasis or recurrence are rare. UTROSCT are considered of uncertain malignant potential and no particular form of treatment is formally recommended, with hysterectomy currently being the treatment of choice. This patient will be followed up for five years during which clinical examination and tomography of the chest, abdomen, and pelvis will be performed annually.